Tailoring Technology-Enhanced Learning Arrangements to Individual Needs - Trapp, Sonja; Thomas, Ludger; Möbs, Sabine (International Journal of Advanced Corporate Learning (iJAC), 2009)
Efficiency and sustainability of technology-enhanced learning is increasingly guaranteed by target-group and subject-specific arrangements of learning-conducive elements. Self-learning phases are combined with synchronous or asynchronous online collaboration and cooperation, as well as with face-to-face training sessions. In the "Up2UML" project funded by the Leonardo-da-Vinci initiative, partners from Ireland, Romania, Bulgaria, France and Germany developed an approach for designing and tailoring learning arrangements for the software modelling domain. This paper describes how such a tailoring can be set up, putting a special focus on the design of learning scenarios (IMS Learning Design) in conjunction with the design of learning media (eduDocBook).